Simulation Analysis of the Working Process of Roller Overrunning Clutch based on ADAMS - Shi Guanglin; Chen Zhangwei; Nie Chao; Zhu Lin (Jixie chuandong)
As the current research about the dynamics of roller overrunning clutch in the transmission system of loader is insufficient,on the basis of virtual prototype technology,the simulation analysis of the working process of loader roller overrunning clutch is carried out. The typical operating conditions of overrunning and wedging of the roller overrunning clutch used by loader are chosen to be analyzed by using the multi-body dynamic stimulation analysis software ADAMS,and consequently several important parameters,such as the response characteristic of spring in overrunning,the engagement time and impact load in wedging etc.,are obtained,which provides reference for a better understanding of the working process of overrunning clutch.